Seasonal malaria chemoprevention in Africa and China’s upgraded role as a contributor: a scoping review - Ming Xu; Yun-Xuan Hu; Shen-Ning Lu; Muhammad Abdullahi Idris; Shu-Duo Zhou; Jian Yang; Xiang-Ning Feng; Yang-Mu Huang; Xian Xu; Ying Chen; Duo-Quan Wang (Infectious Diseases of Poverty, 2023)
Abstract Background Children under five are the vulnerable population most at risk of being infected with Plasmodium parasites, especially in the Sahel region. Seasonal malaria chemoprevention (SMC) recommended by World Health Organization (WHO), has proven to be a highly effective intervention to prevent malaria. Given more deaths reported during the COVID-19 pandemic than in previous years due to the disruptions to essential medical services, it is, therefore, necessary to seek a more coordinated and integrated approach to increasing the pace, coverage and resilience of SMC. Towards this end, fully leverage the resources of major players in the global fight against malaria, such as China could accelerate the SMC process in Africa. Methods We searched PubMed, MEDLINE, Web of Science, and Embase for research articles and the Institutional Repository for Information Sharing of WHO for reports on SMC. We used gap analysis to investigate the challenges and gaps of SMC since COVID-19. Through the above methods to explore China’s prospective contribution to SMC. Results A total of 68 research articles and reports were found. Through gap analysis, we found that despite the delays in the SMC campaign, 11.8 million children received SMC in 2020. However, there remained some challenges: (1) a shortage of fully covered monthly courses; (2) lack of adherence to the second and third doses of amodiaquine; (3) four courses of SMC are not sufficient to cover the entire malaria transmission season in areas where the peak transmission lasts longer; (4) additional interventions are needed to consolidate SMC efforts. China was certified malaria-free by WHO in 2021, and its experience and expertise in malaria elimination can be shared with high-burden countries. With the potential to join the multilateral cooperation in SMC, including the supply of quality-assured health commodities, know-how transfer and experience sharing, China is expected to contribute to the ongoing scale-up of SMC. Conclusions A combination of necessary preventive and curative activities may prove beneficial both for targeted populations and for health system strengthening in the long run. More actions are entailed to promote the partnership and China can be one of the main contributors with various roles.